Stability Study of Four Layer Aurivillius Oxide of AxBi4-xTi4O15 (A = Ca, Sr, Ba): Atomistic Simulation - Akram La Kilo; La Alio; La Ode Aman; Jafar La Kilo (Chemistry Education Program, the University of Mataram, 2020)
Aurivillius is bismuth layered structure ferroelectrics that can be applied as memory, sensor, and catalyst. This research aimed to study the stability of AxBi4-xTi4O15 Aurivillius (A = Ca, Sr, and Ba). Dopants (A) partially substitute Bi at the sites of Bi(1) and Bi(2) of the perovskite layer. This research method is an atomistic simulation using by the GULP code. Simulations were carried out by means of AxBi4-xTi4O15 geometry optimization at constant pressure, using the Buckingham potential. The results showed that the increase in the concentration of dopants substituting Bi accompanied by an increase in lattice energies. The most stable Aurivillius was CaxBi4-xTi4O15 (x = 16.3%) carried out by Bi substitution at Bi(2) site, with lattice energy, -1668.227 eV. Aurivillius stability decreases by increasing the size of the dopant. The maximum concentration number of A dopant substituting Bi was discussed.